PEMBERDAYAAN MITRA DENGAN PENDAMPINGAN VAKSINASI ND LASOTA-2 UNTUK AYAM PETELUR DAN ND LASOTA-1 UNTUK DOC AYAM PEDAGING DI KELURAHAN WAILITI - Paulus Oktavianus Pyo; Arkadius Suban Keray; Maria Yohanista; Sarlina Noni; MariaAntoniaYersiDuaBura; Diana Genista Siga; Matheus Mbele Dede (LPPM ITB AAS Indonesia Surakarta, 2026)
This livestock business faces various challenges, including infectious diseases such as Newcastle Disease (ND), which causes mass mortality, decreased egg production, and suboptimal growth. Vaccination is often not carried out optimally in small-scale farms due to a lack of knowledge about the schedule and techniques of vaccination, limited access to vaccines, and minimal assistance. The purpose of this community service activity is to assist Partner Farmers in implementing vaccinations that can be carried out appropriately in terms of timing, dosage, and technique, as well as applying good maintenance and biosecurity management, thereby improving the sustainability of smallholder farming in a safe, efficient, and productive manner, and contributing to improving food security and the economic welfare of the local community. This community service activity was carried out using a participatory and community empowerment approach. The stages of the activity were survey and problem identification, socialization and technical education, training and vaccination assistance, and implementation of vaccination at partner farms. The results of the community service activity on surveys and problem identification found that the profile of partner farmers was smallholder farmers with medium-scale businesses. Basic knowledge of livestock health management varied, and farmers had a poor understanding of the appropriate vaccination schedule. The laying hen and broiler chicken coops owned by partners are semi-open, with adequate ventilation but suboptimal sanitation. The health status of the partners' livestock shows a history of respiratory disease in chickens in the last 6 months, which is suspected to be related to ND disease, and there are no systematic livestock health records among farmers. The results of the ND vaccination socialization and education program covered the importance of ND prevention, agreement on the LaSota-2 ND vaccination schedule for laying hens, LaSota-1 ND vaccination for broiler chicks, eye drop vaccination techniques, and coop biosecurity standards. The results of the assistance and implementation of vaccination were carried out over 2 days, namely checking health conditions before vaccination, preparing vaccines and solvents, administering ND vaccines to 16-week-old laying hens using the LaSota-2 ND vaccine at a dose of 0.5 ml/head, using the intramuscular injection method in the thigh (injection), 6-day-old broiler chicks using the LaSota-1 ND vaccine at a dose of 0.25 ml/bird, and the eye drop method. A total of 9,000 chickens were vaccinated, consisting of 5,500 laying hens and 3,500 broiler chicks. Keywords: Partner; vaccination; Wailiti; Newcastle Disease; Broiler Chicken; Laying Chicken